(untitled) (Conferencea, 2024)
This paper discusses the synthesis of chalcogenide materials using thermal evaporation in vacuum conditions, emphasizing the advantages of this method in achieving high-quality thin films. Chalcogenides, known for their diverse applications in electronics, photovoltaics, and thermoelectric devices, are effectively fabricated through controlled thermal evaporation, which allows for precise manipulation of film properties such as thickness, crystallinity, and surface morphology. The review highlights recent advancements in the field, including the impact of post-deposition treatments and the scalability of the thermal evaporation process, providing insights into future research directions.